The Effect of Skipping Exercise on the Ability to Jump Shoot in the Basketball Game of Male Students at SMP Negeri 4 Lahat - Hikmah Lestari; Andrias Pratama; Ary Sandy; Ardiansyah Putra; Risky Darmawan (Performa, 2023)
Basketball is a type of sport that is popular in the community and its development is so fast, and attracts a lot of attention in human life, especially young people. This basketball game grows and develops quickly because this type of basketball game is very fun. Based on research from the results of the championship basketball competition at an early age that was attended by SMP Negeri 4 Lahat, there were many deficiencies, in terms of physical, technical, tactical and mental basis in competing. But not only that, Jump Shoot Basketball is also difficult, because it requires correct basic basketball techniques. One way to overcome this is to improve the basic Jump Shoot movements for these students, so that researchers are interested in providing Skipping exercises with the aim of getting a good Basketball game. This study uses a true experimental research design (True experiment) because this study uses 3 principles, namely randomization, replication, and the existence of control or comparison groups/treatments. First of all, the measurement (pre-test) is then given the treatment and finally the final test (post-test) is carried out. Skipping exercises can increase the ability to jump shoot results in basketball games for male students at SMP Negeri 4 Lahat, this can be seen from the increase in the average pretest of the experimental group, namely 5.3 and the average posttest of the experimental group after being given treatment, which is 8.6. . Thus "There is an effect of Skipping training on Jump Shoot ability in basketball games for male students at SMP Negeri 4 Lahat" can be accepted.